Superselective embolisation of bilateral superior vesical arteries for management of intractable hematuria in context of metastatic bladder cancer - Ahmed Saadi; Abderrazak Bouzouita; Mohamed Hedi Rebai; Mohamed Cherif; Walid Kerkeni; Haroun Ayed; Amine Derouiche; Hatem Rajhi; Riadh Ben Slama; Najla Mnif; Mohamed Chebil (Asian Journal of Urology)
Hematuria due to locally advanced or metastatic bladder cancer is a common condition and is often a management problem. Percutaneous embolisation is a mini-invasive option to handle this situation. We report a case of a patient with a metastatic bladder cancer and who presented with an abundant hematuria and severe anemia. After failure of endoscopic resections and “flush” of radiotherapy haemostatic and refusal of cystectomy by the patient, he was treated by superselective embolisation of bilateral superior bladder arteries with excellent immediate results. The technique is safe and effective in the short term. The long-term effectiveness requires further investigation.